LAWSUIT FOR UNLAWFUL ACTS OF EXECUTION OF FIDUCIARY GUARANTEES IN LEASE ACTIVITIES - Kosasih, Johannes Ibrahim (Warmadewa Press, 2021)
Constitutional Court Decision No. 18/PUU-XVII/2019 dated January 6, 2020, caused a polemic in practice, both among legal experts and business people. The Panel of Judges of the Constitutional Court (MK) made a phenomenal decision which abolished the institution for the execution of guarantees listed in Article 15 paragraphs (2) and (3) of Law Number: 42 of 1999 concerning Fiduciary Guarantees or known as parate executions. Parate Execution is a preferential right for the lessor in financing leasing in the event that the lessee commits an act of default. The decision of the Constitutional Court (MK) stated that the lessor's action was declared as an unlawful act on the execution of the guarantee stated in the fiduciary guarantee law. The aims of this research are to examine the (1) unlawful acts in contractual relationships in leasing activities and (2) the decision of the Constitutional Court (MK) No 18/PUU-XVIII/2019 on the re-interpretation of the constitutionality of Article 15 paragraph (2) on the phrase â€œexecutory powerâ€ and â€œsame as a court decision that has obtained permanent legal forceâ€. This research is normative juridical with a conceptual approach, legislation and cases. The findings in the study explained that the panel of judges considered that the lessorâ€™s action in withdrawing collateral that legally still belongs to the lessor given based on the principle of trust (fiduciary) is an act against the law and ignores the contractual relationship that occurs between the parties.